Successful TQM Implementation in Sri Lankan Public Hospitals - Kaluarachchi, S.P. (My University, 2009)
The study reported in this paper examines how the TQM implementation efforts of a Sri Lankan public hospital were accomplished alongside an attempt to change its culture. The study revealed that the change in the cultural values of the hospital occurred as a result of the implementation of Japanese 5S-based TQM activities. However, it was the democratic leadership and communication of the CEO that functioned as the intermediating factor for this change. The CEO’s personal values created and maintained an ideal type communication with the different employee categories for the successful integration of TQM activities. Further, the study revealed that the selected national cultural values of Sri Lanka did not constrain the democratic leadership values of the CEO.
Keywords: democratic communication by the CEO; Japanese 5S-based TQM activities; Sri Lankan cultural values; Sri Lankan public hospitals; TQM implementation